Pengaruh Motivasi dan Imbalan terhadap Kepatuhan Pengisian Rekam Medis - M. Tryanza Maulana; Rokiah Kusumapradja; Andry Andry (Syntax Corporation Indonesia, 2022)
Minimum Service Standard (SPM), the hospital in which there is information about the standard of hospital medical record service is the completeness of filling medical records 24 hours after completion of service and completeness of informed consent after obtaining clear information has a standard of 100%. This study aims to analyze the influence of understanding about medical records, attitudes, motivations, rewards and work design to the compliance of doctors in filling medical records at Insan Permata Hospital. This study uses a quantitative approach with a research sample of 30 respondents. Data analysis testing using binary logistic regression. The results of the research obtained there is the influence (simultaneous) understanding, motivation, attitude, rewards, and design of the doctor's work to the compliance of medical record filling. Partially there is an influence of motivation and rewards to the doctor's compliance in the filling of medical records. The variable that most affects compliance is motivation and is followed by rewards. It is recommended that IP Hospitals can provide training on medical records for doctors or nurses